New Problems Methods and Techniques in Quantum Field Theory and Statistical Mechanics (Advances in Statistical Mechanics) - Rasetti Mario G (World Scientific Pub Co Inc, 1990)
During the past few years a striking set of new ideas has bridged in an as unprecedented as fertile way some of the most difficult frontiere questions in the-oretical physics and in mathematics. There comes out a complex picture which leads from soliton theory to the theory of three-manifolds. On the other side, via the relation - well known to topolpgists - between braids and links, the pathway leads to knot theory.